High Stakes - Johansen, Iris; Rodgers, Elisabeth S. (New York, NY : Hachette Audio, 2021)
Gambler Logan Tanner is drawn into a conflict between two Russian Mafia bosses over the beautiful and innocent Lara Balkon. Logan has been offered valuable information in exchange for getting Lara out of Russia. Tanner is lead to Las Vegas where the person who's hunting Lara now lies in wait for them.
Keywords: Gamblers -- Fiction; Gambling -- Fiction; Organized crime -- Fiction -- Russia; Disclosure of information -- Fiction; Murder -- Fiction -- Investigation; Women private investigators -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Audiobooks